A comprehensive review on advanced trends in treatment technologies for removal of Bisphenol A from aquatic media - Waleed, Sangeen; Haroon, Muhammad; Ullah, Naeem; Tuzen, Mustafa; Rind, Imran Khan; Sarı, Ahmet (Environmental monitoring and assessment, 2024)
Toxic environmental pollutants are considered to be posed a major threat to human and aquatic systems. The fast advancement of the petrochemical and chemical industries has woken up rising worries concerning the pollution of water by contaminants including phenolic Bisphenol A (BPA), an endocrine-disrupting chemical (EDC). The intermediate BPA used in synthesis of certain plastics, polycarbonate polymers, polysulfone, and epoxy resins of various polyesters. Due to potential health risks, severe toxicity, and widespread distribution, there is an urgent need to develop efficient techniques for the removal of BPA. Therefore, advance management for the active elimination of BPA prior to its release into the water sources is of serious concern. Degradation, membrane separation, adsorption, and biological treatments have been extensively examined as they are easy to operate and cost-effective for effective BPA removal. In this review, we summarized the mechanism and performance for removal of BPA by several sorbents, including natural polymers, natural inorganic minerals, porous and carbon-based materials. Comparative results revealed that composite materials and modified adsorbents have good performances for removal of BPA. Furthermore, kinetic study investigating adsorption mechanisms was also discussed. Hazardous quantities of such types of chemicals in various samples have thus been the subject of increasing concern of investigation. This review clarified the extensive literature regarding the major health effects of BPA and its advanced treatment technologies including biological treatment by natural and synthetic materials have been discussed briefly. It delivers regulation for future development and research from the aspects of materials functionalization, development of methods, and mechanism investigation that directing to stimulate developments for removal of emerging contaminants.